Economical implications and the impact of gonadotropin-releasing hormone administration at the time of artificial insemination in cows raised in the extensive system in North Romania - Berean, Daniel; Bogdan, Liviu Marian; Opris, Petrică; Cimpean, Raluca (Frontiers in Veterinary Science, 2023)
Artificial insemination (AI) is the first and the most used biotechnologies in reproduction all over the world. Many studies reported the beneficial role of gonadotropin-releasing hormone (GnRH) administrated some hours before the AI or at the artificial insemination time. This study aimed to assess the effect of GnRH analogs given at the time of insemination on the first, second, and third AIs and to assess the economical implications of GnRH administration. We hypothesized that administration of GnRH at the time of insemination would increase ovulation and pregnancy rate. The study was conducted on small farms in northwestern Romania and included animals of the Romanian Brown and Romanian Spotted breeds. Animals in estrous at the first, second, and third inseminations were randomly divided into groups that received GnRH at insemination and groups that did not. A comparison between the groups was performed and the cost of GnRH administration to obtain one gestation was calculated. The GnRh administration increased the pregnancy rate at the first and the second inseminations by 12 and 18%, respectively. For one pregnancy, the cost of GnRH administration was approximately 49 euros for the first insemination group and around 33 euros for the second insemination group. No improvement of the pregnancy rate was observed after the GnRH administration for the cows at the third insemination, so, for this group, no economic statistics were performed.